FORMATION OF PROFESSIONAL QUALITIES OF THE FUTURE STUDENT LEADER MUSICAL AND INSTRUMENTAL BANDS - T.M. Plyachenko (Academy of Cognitive and Natural Sciences, 2022)
The author of the article develop the complex of professional qualities of future leader of student's orchestras and instrumental bands. His constituents - personality qualities, capabilities , knowledges, skills, abilities are analysedю